Physical inactivity promotes detrimental effects on body composition and strength performance in older and young females - Hernandez-Martínez, Jordan (2023)
This study aimed to describe and compare the body composition (SMM and body fat), handgrip strength, and countermovement jump (CMJ) between young and older females. A descriptive-comparative study, which evaluated 101 females distributed in: older physically active females (Old-PA; n = 26); older physically inactive females (Old-PI; n = 25); young physically active females (You-PA; n = 25) and; young physically inactive females (You-PI; n = 25). Anthropometry, body composition, handgrip strength, relative strength, and CMJ were assessed following previous recommendations. The main results indicate that the Old-PA have greater SMM and body fat compared to Old-PI (p <0.01), and You-PA vs. You-PI and Old-PA (p <0.01). The You-PA had a higher handgrip strength (p <0.01) than the Old-PA, You-PI, and Old-PI. The Old-PA showed a higher handgrip strength vs Old-PI (p <0.01). The Old-PA presented a higher relative strength vs Old-PI (p <0.01), the You-PA vs You-PI (p <0.01), and the You-PA vs Old-PI (p <0.01). The Old-PA have a higher height in CMJ compared to the Old-PI (p <0.01), You-PA vs. You-PI (p <0.01), and Old-PA vs. You-PI (p <0.01). The physically inactive condition is related to decreases in SMM, handgrip strength and CMJ in young and older females.